The UTAUT Model for Measuring Acceptance of the Application of the Patient Registration System - Tugiman Tugiman; Herman Herman; Anton Yudhana (MATRIK : Jurnal Manajemen, Teknik Informatika dan Rekayasa Komputer, 2023)
The Covid-19 pandemic forced hospitals to innovate so that services comply with health protocols in the new adaptation period. Electronic Health (E-Health) such as online patient registration is expected to be a solution for hospitals with high patient visit rates. The purpose of this study was to analyze the level of user acceptance and the factors that influence the implementation of the online patient registration system for hospital patients. This research was conducted at PKU Muhammadiyah Gombong Hospital, which has implemented an online patient registration system based on Android since May 2020. The evaluation model uses Unified Theory of Acceptance and Use of Technology(UTAUT) and the analysis uses the Structural Equation Model (SEM) method using smart PLS. The results of the research show that all the hypotheses formed show valid values. So it can be said that the application of SIPENDOL in hospitals has been well received by users.